Complications Associated with Loco-Regional Treatment of Breast Cancer and Their Impact on Quality-of-Life - GÜLLÜOĞLU, MAHMUT BAHADIR (AVES, 2019)
Objective: Aim of this prospective study was to determine the complications of different treatment modalities for breast cancer and assess their impact on patients' quality-of-life and psychological status. Materials and Methods: Patients surgically treated for early-stage breast cancer were enrolled in the study. Complications after treatment and quality-of-life parameters were measured and recorded. Results: 218 patients, all female with a median age of 48 (19-82) years, were included in the study. In early period, significant limitation of shoulder movements, increased pain and decreased in functional capacity were observed, whereas in mid-term, all shoulder movements, as well as pain and functional capacity returned normal. In both early period and mid-terms, anxiety scores were significantly decreased, whereas depression scores were significantly increased. In early period, there was a significant decrease in physical and mental area scores. Social area scores were significantly increased, whereas environmental, mental and physical area scores were significantly decreased in mid-term and late period. Conclusion: Overall, patients' quality-of-life was found to be significantly deteriorated in both early period and mid-term and returned to pretreatment period at long term follow up.
Keywords: Breast cancer; quality-of-life; chronic pain; axillary dissection; radiotherapy; LYMPH-NODE DISSECTION; AXILLARY DISSECTION; LATE MORBIDITY; PHASE-III; BIOPSY; MASTECTOMY; TRIAL; STATISTICS; DEPRESSION; RESECTION